Contemplating Religious Forms of Life - Burley, Mikel (Bloomsbury Publishing, 2012)
Ludwig Wittgenstein (1889-1951) made profound contributions to many areas of philosophy and cultural understanding, and his thought and methods have inspired numerous inquirers into the forms of our religious life. D. Z. Phillips (1934-2006) pioneered the application of Wittgenstein-influenced approaches to the philosophy of religion, and emphasized the contemplative, non-dogmatic nature of the philosophical task. In Contemplating Religious Forms of Life, Mikel Burley elucidates and critically examines the work of these two philosophers in relation to various aspects of religion, including rit